P93 NFκB activation by TLR agonists is deficient in macrophages lacking STAT2. (6th September 2011) - Alazawi, W; Gamero, A; Heath, H; Smith, P; Jacobs, M; Waters, J; Foster, G R
Abstract : Introduction: Engagement of Toll-like receptors (TLRs) is an important initiator of the innate immune response in inflammatory liver diseases and leads to release of a range of inflammatory cytokines. TLRs signal through divergent signal transduction pathways but the majority lead to activation of members of the NFκB family. STAT2 is an essential component of canonical signalling through the type I and type III interferon (IFN) receptor but, unlike other members of the Stat family, is not believed to be involved in other signal transduction pathways. Aim: We examined the role of STAT2 on inflammatory signalling. Results: Loss of STAT2 markedly reduced immortalised macrophages' response to a range of TLR agonists (lipopolysaccharide (LPS), poly I:C and IL-1)—production of TNFα and RANTES proteins and a range of inflammatory mRNAs were decreased. The reduction in inflammatory cytokine production could be reversed by reconstitution with STAT2 but blockade of type I IFN signalling did not reproduce the phenotype. Restoration of the normal response to LPS could be achieved with tyrosine phosphorylation defective STAT2 indicating that STAT2 interacts with these signalling pathways without phosphorylation on Tyr690. The multiplicity of STAT2′s effect suggests a common defect to these signalling pathways. There were no abnormalities in the activation of early signalling components in the absence of STAT2, however, levels of phosphorylated IκB, although not total IκB, were reduced in STAT2 −/− cells. Phosphorylation of this inhibitor of NFκB leads to its degradation and release of NFκB proteins into the nucleus. We found that translocation of the NFκB protein p65 into the nucleus and its subsequent binding to DNA was impaired in STAT2 deficient cells. Conclusion: These data suggest that STAT2 is a critical component of the TLR signalling response to early inflammatory stimuli, in particular through maintaining the normal phosphorylation of IκB.